PEMODELAN SISTEM INFORMASI BEBANTENAN DALAM KAITANNYA DENGAN UPACARA YADNYA - Oka Sudana, Anak Agung Kompiang; Ayu Putri, Gusti Agung (Jurnal Teknologi Elektro; Vol 8 No 1 (2009): Jurnal Teknologi Elektro, 2012)
Yadnya Ceremony is a religious ceremony that frequently being held by Hindunese in Bali, which is an offering or a holy sacrifice to Ida Sang Hyang Widhi Wasa, to the Resis, to the Ancestors, to fellow humans, or to the Bhuta Kala. In this Yadnya Ceremony, many bantens and other ceremony requirement are used. But these days many people doesn't quite understand about bebantenan and the Yadnya Ceremony itself. This is caused by lack of information about bebantenan and Yadnya Ceremony that is quite hard to get. So it is needed to build a system for the people to make the information searching easier, one of the ways are building a Web based Bebantenan Information System about Yadnya Ceremony Practice. The designing of information system is done by modeling it using the tree method. Other than that, a modeling using normalitation technique also being used. The analysis that were being done are uploading the application to the internet, user interface analysis, data growth analysis, and system feasibility analysis. After the upload process, the application is being tested and it is running well. The data growth that occur is not too big because the bebantenan and yadnya ceremony data won't change significantly from time to time. So the application program that's being made still can run well and the people can easily gain information about bebantenan and yadnya ceremony where ever they are.